EFEKTIFITAS PENGGUNAAN APLIKASI ZOOM SEBAGAI MEDIA PEMBELAJARAN MASA PANDEMI COVID-19 DI KAMPUS IPDN SUMATERA BARAT - ' Dedi Robandi, Darmansyah, Fetri Yeni, J (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2020)
Abstract The Indonesian government in an effort to prevent the spread of the Covid-19 pandemic issued regulations for all students to carry out online-based learning. IPDN campus is one of the official colleges that implements an online-based learning process using various media, one of which is the zoom application. The effectiveness of online-based learning needs special attention so that the online learning process can continue effectively. This study aims to determine the effectiveness of learning through the Zoom application at the IPDN Campus of West Sumatra. This study uses a qualitative method with data collection techniques through interviews through the WhatsApp application. Based on the results of this study, it is found that the learning process through zoom media is effective. With online learning, the IPDN Praja is more independent and motivates the IPDN Praja to be more active in their recovery, besides that in the lecture process, the IPDN Praja lecture will better understand and accept the material well.Keywords: Learning, Covid-19, Online